Penerapan Modul Gambar Teknik Listrik berbantuan Software AutoCAD - Rundi, Amos; Hambali, Hambali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research was motivated by the application of electrical engineering drawing modules assisted by AutoCAD Software in improving student learning outcomes, as well as limitations in terms of procurement of learning media for the Electrical Engineering Drawing course and Lack of student understanding of the material provided will hurt students. Some of the students cannot imagine and cannot explain the meaning of the picture. This research aims to improve student competence in electrical engineering drawing courses assisted by AutoCAD Software. This study used a quantitative descriptive research method. The subject of this study is a student of Electrical Engineering Education at 2022 Faculty of Engineering UNP. Based on the results of the study, the validity of the media was obtained with valid categories where the learning module is feasible to use. In the student practicality test, it can be concluded that students provide very practical values. So it can be concluded that the electrical engineering drawing module assisted by AutoCAD Software can improve student competence and learning outcomes and is feasible to be applied in the AutoCAD Software-assisted electrical engineering drawing course at the Department of Electrical Engineering Education, Padang State University.